(untitled) (Revista Contexto & Saúde, 2026)
Objetcive: To analyze cervical cancer screening in adolescent girls in a northeastern capital city from 2018 to 2022. Methods: This is a descriptive and ecological study with a quantitative approach using data extracted from the Cancer Information System database of the Ministry of Health, regarding cervical cancer screening tests performed on adolescents in the municipality of Maceió between 2018 and 2022. Results: The data show a record of 11,099 screening tests performed, predominantly female adolescents of Asian descent. It reveals that 100% of the records show unknown schooling, and indicates that screening is the primary reason for screening in the 10-19 age group. Regarding prior screening, non-screening predominates among those aged 10 to 14, while prior screening is more prevalent among those aged 15 to 19. This same age group shows a predominance of results with benign inflammatory and metaplastic changes. Conclusion: The analysis of cervical cancer screening among adolescents in a capital city in Northeast Brazil, from 2018 to 2022, revealed low adherence to preventive actions, reflecting weaknesses in cytopathological examination coverage in this age group.